Average maternal hemoglobin decline after first elective cesarean section compared to higher order cesarean sections. Issue 1 (13th April 2022) - Michaan, Nadav; Madar, Dotan; Kern, Guy; Cohen, Aviad; Many, Ariel; Yogev, Yariv; Grisaru, Dan; Laskov, Ido
Abstract: Introduction: Lower uterine segment scarring after cesarean section can decrease intraoperative bleeding during subsequent surgery. We examined whether first elective cesarean section is associated with greater average blood loss compared to repeated surgery. Methods: Decrease in maternal hemoglobin and hematocrit after surgery was retrospectively compared between three study groups, women in their first, second and third or more cesarean section. Surgery length and need for blood transfusion were also compared. Results: Out of 9401 cases reviewed between January 2010 November 2020, 3917 had a first cesarean section, 3159 s cesarean section and 2325 had a third or more cesarean section. Hemoglobin and hematocrit drops were highest after first cesarean section (1.1 vs 1.0 vs 1.0 mg/dL, P <  0.001 and 3.3 vs 3.0, vs 2.9%, P <  0.001, respectively). Surgery length was significantly longer and more patients after third cesarean section required blood transfusions (2.5% vs 1.4% vs. 0.8%, P <  0.001). First cesarean section, younger age and BMI >35 were associated with increased hemoglobin drop in univariate and multivariate analysis. Conclusions: Although repeated cesarean section is associated with longer surgery and higher need for blood transfusion, average hemoglobin drop after first cesarean section is higher. Scarring of the lower uterine segment can explain this paradoxical finding. Synopsis: First elective cesarean section is associated with a higher average hemoglobin decline compared to higher order surgery.